Who makes the law the Supreme court, Congress, the states and society - Cheney, Timothy D. (Prentice Hall, 1998)
Who Makes the Law explores who really makes the law in our society. Using actual cases, it presents the political and societal responses to Court decisions and uncovers a disparity between the theory that the Court is the final say on law and the reality. This book provides a foundation for understanding the function and impact of the U.S. Supreme Court in our lives and how Court opinions both help and hinder the legislative process. It demonstrates the strength of the U.S. Constitution as well as the difficulty of legislating social issues by presenting attempts by Congress to amend the Constitution and write laws in response to actual Court decisions. It reveals the evolutionary process of law and the effect of public opinion through the response of the States and Society to Court decisions. A valuable book for anyone who wants to understand the interaction of lawmakers, public opinion, and the U.S. Supreme Court.